An analysis of animal health and veterinary facilities in coping the climate change in Bangladesh: what education system can offer for the benefit - Al-Amin, Abul Quasem; Alam, Gazi Mahabubul; Othman, Abdul Jalil (Academic Journals Inc., 2011)
The current situation of climate change related to animal health impacts, overall awareness, mapping of livestock and national policy in these regards are needed an especial scholarly attention in Bangladesh. The national policy primarily fails to deal with the impacts of climate change on animal health and its danger sine it is virtually invisible tha the others harming events such as natural disasters. Therefore, this study addresses some issues generated through an analysis of animal health and veterinary facilities in coping with the climate change and also answer on how a sound effective policy can develop by overcoming the issue. This study focuses the lack of inter-linkage of national policy and planning including the shortcomings of current veterinary education system to bring together the climate change issue and impacts on animal health. The experiences of this study may utilize for climate change related to animal health impacts and a way forward for potential veterinary policy in Bangladesh.